The relative role of patient physiology and device optimisation in cardiac resynchronisation therapy: A computational modelling study. (July 2016) - Crozier, Andrew; Blazevic, Bojan; Lamata, Pablo; Plank, Gernot; Ginks, Matthew; Duckett, Simon; Sohal, Manav; Shetty, Anoop; Rinaldi, Christopher A.; Razavi, Reza; Smith, Nicolas P.; Niederer, Steven A.
Abstract: Cardiac resynchronisation therapy (CRT) is an established treatment for heart failure, however the effective selection of patients and optimisation of therapy remain controversial. While extensive research is ongoing, it remains unclear whether improvements in patient selection or therapy planning offers a greater opportunity for the improvement of clinical outcomes. This computational study investigates the impact of both physiological conditions that guide patient selection and the optimisation of pacing lead placement on CRT outcomes. A multi-scale biophysical model of cardiac electromechanics was developed and personalised to patient data in three patients. These models were separated into components representing cardiac anatomy, pacing lead location, myocardial conductivity and stiffness, afterload, active contraction and conduction block for each individual, and recombined to generate a cohort of 648 virtual patients. The effect of these components on the change in total activation time of the ventricles (ΔTAT) and acute haemodynamic response (AHR) was analysed. The pacing site location was found to have the largest effect on ΔTAT and AHR. Secondary effects on ΔTAT and AHR were found for functional conduction block and cardiac anatomy. The simulation results highlight a need for a greater emphasis on therapy optimisation in order to achieve the best outcomes for patients. Highlights: Ventricular conduction block indicates patient response to CRT. Placement of CRT pacing leads strongly affects response to therapy. Improved treatment planning should be prioritised in order to maximise CRT outcomes.